2012
DOI: 10.1055/s-0032-1325601
|View full text |Cite
|
Sign up to set email alerts
|

Zeitmessstudien im Krankenhaus

Abstract: Zusammenfassung Zielsetzung: Der vorliegende Artikel gibt einen ?berblick ?ber Zeitmessstudien in Krankenh?usern in Deutschland. Methodik: Die Autoren haben in den letzten Jahren mehrere umfangreiche Zeitmessstudien in Krankenh?usern durchgef?hrt. Auf Grundlage dieser Erfahrungen werden die wichtigsten Anwendungsfelder sowie die Verfahren der Zeitmessung und der statistischen Auswertung der gewonnenen Daten diskutiert. Ergebnisse: Zeitmessstudien werden in deutschen Krankenh?usern insbesondere eingesetzt, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The main characteristics of the system are: Arrivals: How many calls come in a certain period of time and according to which distribution? It has been shown that most arrivals follow a Markov process and are Poisson distributed [ 15 ]. Channels: The number of parallel channels (k) determines how many clients can be serviced at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristics of the system are: Arrivals: How many calls come in a certain period of time and according to which distribution? It has been shown that most arrivals follow a Markov process and are Poisson distributed [ 15 ]. Channels: The number of parallel channels (k) determines how many clients can be serviced at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature there are indications that the time expenditure for documentation has increased in the course of time [5]. Although working time analyses are also becoming more important in hospitals [6], a lack of studies from the 1980s or 1990s, which would be necessary for direct comparisons, has been reported [7]. The reasons mentioned in the literature for the increases in administrative tasks, on the other hand, are manifold.…”
Section: Expense For Clinical Documentation Of Inpatients: Extent Andmentioning
confidence: 99%
“…In comparison to the available literature, this study takes possible specialty (gynaecology and obstetrics) and regional characteristics more strongly into consideration and at the same time widens the perspectives of described research results since the previously available studies concentrated principally on the university setting [12]. In addition, this survey showed that working time analyses not only can be applied in the framework of hospital cost calculations and process optimisation but also provide support in the field of personnel management [6].…”
Section: Structure Of the Evaluated Working Timeinpatientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to acquire a deeper understanding of the IA/IgG therapy and the gene expression analysis, which is necessary for deciding, whether this therapy is adequate, the cost project was implemented by two sub-studies. Both were based on the time study approach (Fehrle et al 2013).…”
Section: Study Site and Datamentioning
confidence: 99%